That Escalated Quickly—Planning to Ignore RPE Can Backfire - Bieleke, Maik; Wolff, Wanja (Frontiers in Physiology, 2017)
Ratings of perceived exertion (RPE) are routinely assessed in exercise science and RPE is substantially associated with physiological criterion measures. According to the psychobiological model of endurance, RPE is a central limiting factor in performance. While RPE is known to be affected by psychological manipulations, it remains to be examined whether RPE can be self-regulated during static muscular endurance exercises to enhance performance. In this experiment, we investigate the effectiveness of the widely used and recommended self-regulation strategy of if-then planning (i.e., implementation intentions) in down-regulating RPE and improving performance in a static muscular endurance task. 62 female students (age: M = 23.7 years, SD = 4.0) were randomly assigned to an implementation intention or a control condition and performed a static muscular endurance task. They held two intertwined rings as long as possible while avoiding contacts between the rings. In the implementation intention condition, participants had an if-then plan: "If the task becomes too strenuous for me, then I ignore the strain and tell myself: Keep going!" Every 25±10 seconds participants reported their RPE along with their perceived pain. Endurance performance was measured as time to failure, along with contact errors as a measure of performance quality. No differences emerged between implementation intention and control participants regarding time to failure and performance quality. However, mixed-effects model analyses revealed a significant Time-to-Failure × Condition interaction for RPE. Compared to the control condition, participants in the implementation intention condition reported substantially greater increases in RPE during the second half of the task and reached higher total values of RPE before task termination. A similar but weaker pattern evinced for perceived pain. Our results demonstrate that RPE during an endurance task can be self-regulated with if-then plans. This finding is particularly important given how frequently RPE is used in exercise science as a correlate of physiological processes that ultimately limit performance. Unexpectedly, participants with implementation intentions reported higher RPE than control participants. This suggests that strategies to self-regulate RPE might have ironic effects that hamper performance, maybe by increasing attention to RPE. This implication is important for exercise physiologists, athletes and coaches.